2010
DOI: 10.1097/mlr.0b013e3181c16203
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Use of Electronic Health Record Features and Health Care Quality

Abstract: Consistent with past studies, there was no significant relationship between use of EHR as a binary factor and performance on quality measures. However, availability and use of specific EHR features by primary care physicians was associated with higher performance on certain quality measures. These results suggest that, to maximize health care quality, developers, implementers and certifiers of EHRs should focus on increasing the adoption of robust EHR systems and increasing the use of specific features rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
2
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 19 publications
4
81
2
2
Order By: Relevance
“…Several previous studies found no effect. [6][7][8][9][10] Others found modest effects for some, but not all, of the quality measures considered. [11][12][13] Still others were positive, but took place mostly in academic medical centers or integrated delivery systems with home-grown, rather than commercially available, EHRs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies found no effect. [6][7][8][9][10] Others found modest effects for some, but not all, of the quality measures considered. [11][12][13] Still others were positive, but took place mostly in academic medical centers or integrated delivery systems with home-grown, rather than commercially available, EHRs.…”
Section: Introductionmentioning
confidence: 99%
“…5,14 Few studies have taken place in communities with multiple payers and commercially available EHRs, which are typical of most American communities. 15 Previous studies have also been limited by nonuniversal use of concurrent control groups, 12 lack of adjustment for patient case mix, [6][7][8][9][10][11][12][13] and small or unknown sample sizes of patients per quality measure per physician. [6][7][8][9][10][11][12][13] We sought to determine the effect of commercially available EHRs on ambulatory quality in a multi-payer community, while addressing many of the other limitations of the previous literature.…”
Section: Introductionmentioning
confidence: 99%
“…Much recent research and practice focuses on developing integrated EMRs (Poon et al, 2010;Resnick et al, 2004;Wang et al, 2009). Based on principles of inter-operability, such systems allow the sharing of health-related information across geographically distributed healthcare workers and administrators.…”
Section: Discussionmentioning
confidence: 99%
“…3 As part of Stage 1 and 2 "meaningful use" guidelines, providers are required to actively "maintain an upto-date problem list of current and active diagnoses," with 80% of patients having at least one problem recorded or an indication of no known problems. 4,5 However, research has shown that problem lists are frequently inaccurate and out-of-date. [6][7][8][9][10] In a previous study, we demonstrated that common problems were frequently omitted from the problem list at one large hospital network-completeness ranged from 4.7% for renal disease to a maximum of 78.5% for breast cancer.…”
Section: Introductionmentioning
confidence: 99%